Tinjauan Hukum Islam Terhadap Tradisi Tepuk Tepung Tawar Pada Adat Pernikahan Melayu Bengkalis - Al Mansur, Muhammad; Asfar Hamidi Siregar; Rizki Aulia Nasution; Nurul Safika (Akademika : Jurnal Keagamaan dan Pendidikan, 2025)
Tepuk tepung tawar is a traditional Malay wedding ceremony which aims to ask for protection and safety for the bride and groom as well as the smooth running of the event. It is important to preserve this ancestral heritage, because every material used has a deep meaning, showing the strong connection between the Malay people and nature. This research adopts descriptive qualitative methods through field research. Data was collected by direct observation, interviews, and documentation from traditional leaders in Bengkalis, in order to understand the procession and review of munakahat jurisprudence regarding this custom. As a result, plain flour pats involve the use of natural ingredients and regular traditional processes. Even though it is not in the Qur'an or hadith, the law is mubah (permissible). This is in accordance with the principle of muamalah in Islam, where everything is considered permissible as long as there are no arguments that prohibit it and it does not conflict with religious law.